2001
DOI: 10.1002/ajmg.1551
|View full text |Cite
|
Sign up to set email alerts
|

The phenotypic manifestations of interstitial duplications of proximal 15q with special reference to the autistic spectrum disorders

Abstract: This study investigated the phenotypic manifestations of interstitial duplications of chromosome 15 that involve the Prader-Willi/Angelman syndrome critical region (PWACR). Twenty-one affected individuals from six families were evaluated in detail, using standardized and semi-standardized measures of intelligence, psychopathology, and physical anomalies. Special attention was placed on determining the prevalence of autism spectrum disorders as well as the relationship between the parental origin of the duplica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
183
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(195 citation statements)
references
References 22 publications
11
183
0
1
Order By: Relevance
“…Chromosome 15q11-13 has been suggested to contain a susceptibility gene for autism based on several reports of chromosome abnormalities. 11 More distally, at 51.21 cM, we found association with marker D15S198 and for the two-marker segment D15S198-D15S643, and Shao et al 41 identified a region from 43.5 to 62.4 cM. On chromosome 6q marker D6S1652 (at 92.85 cM) appeared to be associated with autism and related PDDs.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Chromosome 15q11-13 has been suggested to contain a susceptibility gene for autism based on several reports of chromosome abnormalities. 11 More distally, at 51.21 cM, we found association with marker D15S198 and for the two-marker segment D15S198-D15S643, and Shao et al 41 identified a region from 43.5 to 62.4 cM. On chromosome 6q marker D6S1652 (at 92.85 cM) appeared to be associated with autism and related PDDs.…”
Section: Discussionsupporting
confidence: 57%
“…4,5 Based on genome-wide scans, screening of possible candidate genes, and studies of association between autism and chromosome abnormalities, candidate regions of autism have been suggested on chromosome 2q, [6][7][8] 7q, 9,10 and 15q. 11,12 However, no susceptibility genes have yet been identified, and except for a few specific etiological factors like the fragile X syndrome, tuberous sclerosis, and maternally inherited duplication of 15q11-13, the etiology of autism is largely unknown. 13 The use of isolated populations is a powerful approach in the search for disease genes and has facilitated the identification of candidate chromosome regions involved in monogenic diseases 14 and in some complex diseases, for example, uric acid nephrolithiasis.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding additional behavioural problems, a severe hyperactivity is often noticed. [19][20][21][22][23][24][25][26] Deletions of the maternal or paternal chromosome 15q11-13 regions are associated with two cytogenetic imprinting disorders, Angelman syndrome and Prader-Willi syndrome (PWS). Genomic imprinting describes the phenomenon of differences in gene expression between the allele inherited from the mother and the allele inherited from the father.…”
Section: Cytogenetic Findings and Genetic Syndromes In Admentioning
confidence: 99%
“…26 Re-examination of the parents in the case of Browne et al 24 suggests that paternal duplications of 15q11.2-q13 can have phenotypic consequences, but much milder than those associated with maternal duplications of the same segment. 27 The lack of a 'second hit' is likely to explain the lack of retinoblastoma in the mother of a child with the 13q14 deletion. 28 Nevertheless, over half the 56 carriers in this category were phenotypically unaffected.…”
Section: Jck Barber Et Almentioning
confidence: 99%